Pinanga schwanerensis, a new species of Pinanga (Arecaceae) from Kalimantan, Indonesia - Randi, Agusti; Hikmat, Agus; Heatubun, Charlie D. (Phytotaxa, 2019)
A new species of palm, Pinanga schwanerensis, is described and illustrated here. This is the third species of Pinanga to have been described from Kalimantan since the description of P. salicifolia Blume and P. albescens Becc. A discussion of its morphological characters, distribution, ecology, habitat and conservation status is provided.